The cortical activation pattern by a rehabilitation robotic hand: a functional NIRS study - Chang, Pyung Hun; Lee, Seung-Hee; Koo, Kwang-Min; Lee, Seung-Hyun; Jin, Sang-Hyun; Yeo, Sang Seok; Seo, Jeong Pyo; Jang, Sung Ho (Frontiers in Human Neuroscience, 2014)
Introduction: Clarification of the relationship between external stimuli and brain response has been an important topic in neuroscience and brain rehabilitation. In the current study, using functional near infrared spectroscopy (fNIRS), we attempted to investigate cortical activation patterns generated during execution of a rehabilitation robotic hand. Methods: Ten normal subjects were recruited for this study. Passive movements of the right fingers were performed using a rehabilitation robotic hand at a frequency of 0.5 Hz. We measured values of oxy-hemoglobin(HbO), deoxy-hemoglobin(HbR) and total-hemoglobin(HbT) in five regions of interest: the primary sensory-motor cortex (SM1), hand somatotopy of the contralateral SM1, supplementary motor area (SMA), premotor cortex (PMC), and prefrontal cortex (PFC). Results: HbO and HbT values indicated significant activation in the left SM1, left SMA, left PMC, and left PFC during execution of the rehabilitation robotic hand(uncorrected, p< 0.01). By contrast, HbR value indicated significant activation only in the hand somatotopic area of the left SM1 (uncorrected, p< 0.01). Conclusions: Our results appear to indicate that execution of the rehabilitation robotic hand could induce cortical activation.